Outdoor Air Contaminants-Heavy Metals and Associated Health Risks in Duhok-Iraq - Muhyadeen, Samir Hashim; Ramadhan , Revink A. (Science Journal of University of Zakho, 2023)
Toxic elements in the atmosphere can cause a variety of health and environmental problems. The current work aims to assess the concentrations of heavy metals associated with the air in the Duhok city-Kurdistan Region of Iraq. For the first time a low volume sampling pump with Glass Microfiber Filter paper was used. Forty samples of air filter aerosol particles were collected from several areas in the Duhok city, during the dry and rainy seasons. Samples of air filters were prepared by a microwave digestion system and assessed by inductively coupled plasma Optical-Emission Spectrometry (ICP-OES). The average concentrations of Cr, Zn, Ni, Cd, Fe, and Pb found in 20 sites in the study area for the dry season were 0.004 mg/m3, 0.007 mg/m3, 0.003 mg/m3, 0.002 mg/m3, 0.142 mg/m3, and 0.402 mg/m3 respectively. Also, the average levels of the mentioned elements were 0.003 mg/m3, 0.004 mg/m3, 0.012 mg/m3, 0.003 mg/m3, 0.138 mg/m3, and 0.645 mg/m3 respectively in wet season. Seasonal results confirmed no significant differences in the concentrations of elements measured at all study sites, with the exception of lead, which doubles during the rainy season. Results showed that the levels of metal concentrations in the present study exceeded the standard limits of WHO. The results of the health risk assessment showed that the population in Duhok city had a higher lifetime chance of developing cancer as a result of these air concentrations and their heavy metal content.